(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
Religious values ​​are important to instill in facing the challenges of modern developments that can endanger moral integrity. The Amal Saleh Foundation seeks to strengthen the religious values ​​of its activists through taklim activities. However, the low participation and understanding of activists indicate the need for evaluation to improve the effectiveness of these activities. This study aims to determine how the process of implementing taklim activities strengthens the religious values ​​of foundation activists. The research method used is qualitative evaluation with data collection techniques through observation, interviews, and documentation. The results of the study indicate that taklim activities have been carried out in a planned and scheduled manner by the foundation’s management, but have not run optimally due to the lack of awareness and participation from activists. Inhibiting factors in the implementation of taklim activities include the busyness of activists, lack of understanding of the importance of taklim, and weak commitment to the activities. The conclusion of this study shows that although the implementation of taklim activities has not been optimal, this activity still makes a positive contribution to instilling and strengthening religious values ​​in Amal Saleh Foundation activists.